The The Role of Growth in Moderating the Relationship of Intellectual Capital to Firm Values - Komang Adhitanaya; Partiwi Dwi Astuti; Ni Nengah Seri Ekayani (Universitas Warmadewa, 2023)
This study examines the moderating effect of growth on the relationship between intellectual capital and firm value. The population in this study is made up of manufacturing companies in the consumer goods sector that are listed on the Indonesia Stock Exchange in the 2017–2020 period. The determination of the sample using the purposive sampling method yielded a sample of 37 companies. The analytical method used is moderated regression analysis (MRA). The study results reveal that intellectual capital has a significant positive effect on firm value. Furthermore, growth strengthens the effect of positive intellectual capital on firm value. With growth, it can indicate the company's progress through an increase in assets, one of which is intellectual capital that has the potential to generate high cash flows in the future, thereby increasing the value of the company.